Expression of Hemin Receptor Molecule ChuA Is Influenced by RfaH in Uropathogenic Escherichia coli Strain 536 - Nagy, Gábor (American Society for Microbiology, 2001)
The outer membrane protein ChuA responsible for hemin utilization has been recently identified in several pathogenic Escherichia coli strains. We report that the regulatory protein RfaH influences ChuA expression in the uropathogenic E. coli strain 536. In an rfaH mutant, the chuA transcript as well as the ChuA protein levels were significantly decreased in comparison with those in the wild-type strain. Within the chuA gene, a consensus motif known as the JUMPStart (just upstream of many polysaccharide associated gene starts) sequence was found, which is shared by RfaH-affected operons. Furthermore, the presence of two different subclasses of the chuA determinant and their distribution in E. coli pathogroups are described.